2017
DOI: 10.1177/1933719117702251
|View full text |Cite
|
Sign up to set email alerts
|

Current Success and Efficiency of Autologous Ovarian Transplantation: A Meta-Analysis

Abstract: Success rates with cryopreserved OTT have reached promising levels. Given these recent data, ovarian tissue cryopreservation should be considered as a viable option for FP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(146 citation statements)
references
References 51 publications
2
132
0
8
Order By: Relevance
“…21,22 Recent studies also have demonstrated the effectiveness of the technique in patients who have previously undergone chemotherapy, opening FP options to select patients between cycles and after treatment. Laparoscopic unilateral oophorectomy (partial or complete) is the preferred surgical technique.…”
Section: Ovarian Tissue Cryopreservationmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Recent studies also have demonstrated the effectiveness of the technique in patients who have previously undergone chemotherapy, opening FP options to select patients between cycles and after treatment. Laparoscopic unilateral oophorectomy (partial or complete) is the preferred surgical technique.…”
Section: Ovarian Tissue Cryopreservationmentioning
confidence: 99%
“…24 Although slow-freeze techniques for cryopreservation currently are the standard, initial data from more recent studies have shown vitrification (rapid freeze) to be at least comparable if not favored. 21,23,[25][26][27] To the best of our knowledge, all live births to date have used orthotopic transplantation without specific data available regarding the ideal orthotopic location. 20 Studies also have demonstrated successful pregnancies in patients with ovarian tissue specimens that were transported overnight (up to 20 hours) prior to cryopreservation.…”
Section: Ovarian Tissue Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of the stored ovarian tissue to support fertility restoration when the individual wishes to start her family is demonstrated by the delivery of more than 130 healthy babies world wide after autotransplantation of the frozen-thawed tissue and the restoration of endocrine and ovarian function (Pacheco and Oktay, 2017) with more ongoing pregnancies being recorded. Although the overall efficiency of fertility restoration following ovarian tissue preservation and transplantation is unknown, recent evidence from defined cohorts of patients suggests a ~30% live birth rate after autotransplantation of slow frozen-thawed ovarian cortex, (Jadoul et al, 2017;Keden et al, 2018).…”
Section: Ovarian Tissue Preservationmentioning
confidence: 99%
“…When followed by autotransplantation, success rates are high regarding the reestablishment of ovarian activity (63.9%) and natural live births (57.5%), according to a meta-analysis performed in 2017 [12]. …”
Section: Indications For Otcmentioning
confidence: 99%